INOVASI BERKELANJUTAN KEBIJAKAN TOL LAUT DALAM MEMINIMALISIR DISPARITAS HARGA DI INDONESIA: Sustainable Innovations in the Sea Toll Policy for Reducing Price Disparities in Indonesia - Wijaya, Eka (Jurnal Globalisasi Hukum., 2025)
To optimize the use of maritime transportation and reduce price disparities between Western and Eastern Indonesia, the government introduced the Sea Toll policy through Presidential Regulation No. 106 of 2015 concerning the Implementation of Public Service Obligations for Sea Freight Transport. This policy aims to address price imbalances, particularly in Eastern Indonesia, which faces greater logistical challenges. This study uses a normative approach based on the analysis of existing documents and secondary data such as legislation, legal theories, and expert opinions. The findings indicate that the Sea Toll program, since its launch in 2015, has significantly reduced the prices of basic goods in Eastern Indonesia by up to 30%. However, to achieve more optimal price equalization, improvements are still needed in local distribution, strengthening the local logistics ecosystem, increasing return cargo loads, and developing equitable port infrastructure.